Colonial influences and African women's segregation: Evidence from Anglican converts in urban British Africa - Felix Meier zu Selhausen; Jacob Weisdorf (African Economic History Network (AEHN), 2023)
Using educational and occupational statistics derived from 30,000 marriage registers obtained from six major cities in British colonial Africa, we show how early colonial mission education helped African men access formal labour. Women were relegated to informal and homemaking activities instead, even if mission schooling facilitated their social mobility via marriage. The early-colonial rise in gender inequality was followed by a remarkable decline herein after World War II helped by the Africanisation and feminisation of the civil service alongside Western women's liberalisation movement. This process was relatively faster in West Africa where women's pre-colonial economic independence contested colonial ideals of domestic virtue.
Keywords: 330; Anglican; British Africa; Christian Missionaries; education; Gender Inequality; Labour Market; Marriage; Urban